An unusually high upper thermal acclimation potential for rainbow trout. Issue 1 (15th January 2022) - Adams, Olivia A; Zhang, Yangfan; Gilbert, Matthew H; Lawrence, Craig S; Snow, Michael; Farrell, Anthony P
Abstract : We address a crucial question relevant to global climate change and of general interest to ecological and conservation physiologists: does a fish species normally regarded as a cold-loving species have sufficient standing intra-specific variation to form a warm-tolerant population that could perhaps thrive in a warmer world? Abstract: Thermal acclimation, a compensatory physiological response, is central to species survival especially during the current era of global warming. By providing the most comprehensive assessment to date for the cardiorespiratory phenotype of rainbow trout ( Oncorhynchus mykiss ) at six acclimation temperatures from 15°C to 25°C, we tested the hypothesis that, compared with other strains of rainbow trout, an Australian H-strain of rainbow trout has been selectively inbred to have an unusually high and broad thermal acclimation potential. Using a field setting at the breeding hatchery in Western Australia, thermal performance curves were generated for a warm-adapted H-strain by measuring growth, feed conversion efficiency, specific dynamic action, whole-animal oxygen uptake ( Ṁ O2 ) during normoxia and hypoxia, the critical maximum temperature and the electrocardiographic response to acute warming. Appreciable growth and aerobic capacity were possible up to 23°C. However, growth fell off drastically at 25°C in concert with increases in the time required to digest a meal, its total oxygen cost and its peak Ṁ O2 . The upper thermal tipping points for appetite and food conversion efficiency corresponded with a decrease in the ability to increase heart rate during warming and an increase in the cost to digest a meal. Also, comparison of upper thermal tipping points provides compelling evidence that limitations to increasing heart rate during acute warming occurred well below the critical thermal maximum (CTmax ) and that the faltering ability of the heart to deliver oxygen at different acclimation temperatures is not reliably predicted by CTmax for the H-strain of rainbow trout. We, therefore, reasoned the remarkably high thermal acclimation potential revealed here for the Australian H-strain of rainbow trout reflected the existing genetic variation within the founder Californian population, which was then subjected to selective inbreeding in association with severe heat challenges. This is an encouraging discovery for those with conservation concerns for rainbow trout and other fish species. Indeed, those trying to predict the impact of global warming should more fully consider the possibility that the standing intra-specific genetic variation within a fish species could provide a high thermal acclimation potential, similar to that shown here for rainbow trout.